Short Course: Designing multi-projetor VR systems: from bits to bolts - Dias, J.; Soares, L. P.; Raposo, A.; Bruno R. de Araujo (Atas do IEEE VR 2008, 2008)
Immersive multi-projection environments are becoming affordable for many research centres. However, these solutions need several integration steps to be fully operational; some are difficult and not in a common domain. This tutorial presents the most recent techniques involved in multi-projection solutions, from projection to computer cluster software. The hardware in these VR installations is a connection of projectors, screens, speakers, computers and tracking devices. The tutorial will introduce hardware options, explaining their advantages and disadvantages. We will cover software design and open source tools available and how to administrate the whole solution, with tasks such as installing the computer cluster and configuring the graphical outputs. An introduction to tracking systems will also be provided to explain how electromagnetic and optical trackers work. Ultimately, we will present important design decisions in actual cases: the project process, problems encountered, and good and bad points in each decision.